Study on the Effect of Blasting Vibration on Rock Bolt and Shotcrete. Issue 1 (1st January 2022) - Ren, Yanlong; Yang, Xuanli; Li, Chang; Lü, Mingzhe; Zhuang, Jinzhao
Abstract: The blasting tunneling construction method is often used in the underground engineering projects such as tunnels, coal mines roadway, chambers and so on, rock bolt and shotcrete support is used. Although the blasting construction method has many advantages, but also will be accompanied by adverse effects. Blasting vibration of blasting construction not only to the surrounding environment, building (structure) and other adverse effects, but also on the support of the underground project itself has a negative impact. In order to discuss the impact of blasting vibration on shotcrete and rock bolt support in the process of blasting tunneling of roadway, a certain amount of explosives is detonated in the hole of the working face, the finite element software ANSYS/LS-DYNA was used to establish the numerical calculation model, through time history analysis calculation, the distribution law of the vibration velocity on the shotcrete surface along the section and the variation law of the longitudinal tension and compression stress of the rock bolt are obtained. The results show that the blasting vibration produced by blasting tunneling has a great influence on the shotcrete at the shoulder, but little influence on the axial force of the rock bolt.